Robust adaptive beamforming using beam‐space steering vector estimation. Issue 19 (1st September 2013) - Yang, T.; Su, T.; Zhu, W.T.; Zhang, L.
Abstract : To solve the problem of performance degradation owing to imprecise knowledge of the array steering vector and inaccurate estimation of the sample covariance matrix, a novel algorithm based on beam‐space steering vector estimation for robust adaptive beamforming is presented. By using the complementary set of the spatial sector in which the actual steering vector lies, a beam‐space transformation matrix can be constructed to remove the signal of interest from the sampling covariance matrix. The beam‐space steering vector is estimated by solving a non‐convex quadratically constrained quadratic optimisation problem. The effectiveness and robustness of the proposed algorithm is verified by the simulations.